Littoral Maeridae and Melitidae (Amphipoda: Gammaridea) from the Gulf of Tehuantepec, Mexico - Del Socorro García-Madrigal, María (Zootaxa, 2010)
In the Tropical Eastern Pacific region, the gammaridean amphipods of the families Maeridae and Melitidae are represented by 28 species and 11 genera; the genus Elasmopus is the richest, with 13 species. The examination of approximately 3,250 specimens resulted in 12 new records from the Gulf of Tehuantepec, belonging to four genera, Elasmopus, Maera, Quadrimaera and Melita. All species are illustrated and described. Seven new species are described as: Elasmopus bastidai n. sp., Elasmopus karlae n. sp., Elasmopus lecroyae n. sp., Elasmopus marcelae n. sp., Elasmopus oaxaquensis n. sp., Maera umarae n. sp., and Melita bousfieldi n. sp. With these new species the genus Elasmopus from the Tropical Eastern Pacific is increased to 18 species that corroborates the hypothesis of Barnard (1979) “on the Pacific there are (sic) a mark of speciation of genus Elasmopus”. In addition, there are five new records from the Gulf of Tehuantepec: three species of Elasmopus and two of Quadrimaera. Also, the range distribution of Elasmopus temori Barnard and E. zoanthidea Barnard, is increased to the north from the Galapagos Islands to the Gulf of Tehuantepec; for E. tubar Barnard, Quadrimaera chinarra Barnard, and Q. reishi Barnard, there are new intermediate records between the Gulf of California and the Galapagos Islands. With the exception of the species of Quadrimaera, all known species represent the second record in the region after their first descriptions.